P277 SECRET BEYOND THE DOOR. TRIAGE ANALYSIS AND RECOGNITION AT THE DOOR OF ELDERLY PATIENTS WITH PULMONARY EMBOLISM WHO ARRIVE IN THE EMERGENCY ROOM. THE REAL–LIFE EXPERIENCE OF 5 YEARS IN THE EMERGENCY ROOM. (18th May 2022) - Savioli, G; Ceresa, I; Novelli, V; Pagani, M; Belliato, M; Grulli, F; Fumoso, F; Lapia, F; Brattoli, M; Bressan, M
Abstract: Background: The range of symptoms of pulmonary embolism is wide and its recognition difficult. Purpose: to analyze the efficiency of triage in the EP. Methods: Single–center retrospective observational study, on all geriatric patients (>75 years) who entered our ED, where they were diagnosed with acute PE. Enrollment began in 2015 and ended in 2019. We analyzed means of presentation, priority codes for medical examination, exit code, hospitalization needs. We collected data from medical history, physical examination, laboratory tests, imaging, outcomes. Results: We enrolled 247 patients, all in need of hospitalization. 44% came for dyspnea, 17% for chest pain, 16% for signs of DVT, 8% for syncope. 5% had only atypical symptoms (dizziness, general malaise, low–grade fever, neurological symptoms …). 45% had concomitant deep vein thrombosis. 50% showed alteration of the ECG tracing, 49% alteration of the shock index. Only 4% showed hypotension, 13% tachycardia and 8% desaturation. 39% arrived with their own vehicle. 32% was allocated to the area with low intensity of care, 68% to the area with medium–high intensity of care. As regards the priority code for the visit, 0% received a non–urgency code (white code or code 5), 27.9% a minor urgency code (green code or code 4) and 3.6% a high priority to the visit with assignment to low intensity of care (low intensity yellow or code 3). 63.15% received an emergency code (urgency or code 2) and 5.3% an emergency code (red code or code 1). The severity code at discharge, given on clinical criteria, was a low severity code (white or green) in 18% of cases, while 76% was considered high severity (urgency, yellow code) and in 6% for very high gravity (red code). 34% showed massive PE, 32% showed organ damage. 41% were considered to be at high risk of short–term mortality according to European guidelines, 8% required intensive care and in–hospital mortality was 7.7%. Under triage is 32%. Conclusions: The population that arrives in ED due to pulmonary embolism presents extremely varied symptomatological pictures, and an overall high degree of clinical risk and care and therapeutic complexity in spite of the symptoms complained of and vital parameters. Under–riage remains a real problem for ED for this category of patients.